On the Adams–Riemann–Roch theorem in positive characteristic - Pink, R; Rössler, D (Springer, 2011)
Let p > 0 be a prime number. We give a short proof of the Adams–Riemann–Roch theorem for the p-th Adams operation, when the involved schemes live in characteristic p. We also answer a question of B. Köck.